Comparison between Amulet and Watchman left atrial appendage closure devices: A real-world, single center experience. (December 2021) - Saad, Mohammed; Risha, Osama; Sano, Makoto; Fink, Thomas; Heeger, Christian-Hendrik; Vogler, Julia; Sciacca, Vanessa; Eitel, Charlotte; Stiermaier, Thomas; Joost, Alexander; Keelani, Ahmad; Fuernau, Georg; et al.
Abstract: Background: Data reporting a head-to-head comparison between Amulet and Watchman devices are scarce. The aim of this study was to compare the Watchman™ versus Amulet™ left atrial appendage closure (LAAC) devices in a consecutive, industry-independent registry. Methods: Patients who underwent LAAC using Watchman or Amulet devices from January 2014 to December 2019 at the University Heart Center Lübeck, Lübeck, Germany were included in the present analysis. Primary endpoints included periprocedural complications (in-hospital death, pericardial tamponade, device embolization, stroke, major bleeding and vascular access complications), and complications during long-term follow-up (ischemic stroke, hemorrhagic stroke, thromboembolism, device thrombus, bleeding and death). Results: After matching the patients for age (±5 years), gender, CHA2DS2Vasc score (±1) and HASBLED score (±1), each of the Watchman and the Amulet groups included 113 patients. Patients in the Amulet group had significantly more periprocedural complications (2.7% vs 10.6%, p = 0.029; respectively) and more major bleeding complications (0% vs 5.3%, p = 0.029; respectively). During long-term follow-up, the rate of events was comparable between the Watchman and Amulet groups (18.3% versus 20.8%, p = 0.729; respectively). Conclusion: Amulet LAAC device was associated with increased periprocedural complications as compared to Watchman LAAC device. On long-term follow-up, both devices showed comparable efficacy and safety.